Male Predominance of Congenital Malformations in Infants of Women With Type 1 Diabetes - Evers, Inge M. (American Diabetes Association, 2009)
OBJECTIVE: To investigate sex-related differences in maternal, perinatal, and neonatal outcome in type 1 diabetic pregnancies in the Netherlands. RESEARCH DESIGN AND METHODS: This was a nationwide prospective cohort-based study. Logistic regression analysis was used to identify sex-specific risk factors for adverse pregnancy outcome. RESULTS: A total of 323 type 1 diabetic pregnancies were included; 314 were ongoing after 24 weeks of gestation. There were eight twin pregnancies and one triplet, resulting in 324 infants born after 24 weeks of gestation. Multiple logistic regression analysis showed that the occurrence of congenital malformations was independently associated with male newborns (OR 3.5 [95% CI 1.3–10.0]; P = 0.02). CONCLUSIONS: The higher incidence of congenital malformations in infants of women with type 1 diabetes appears to be restricted to male infants only.